Sufficient and Necessary Conditions for Oscillation of th-Order Differential Equation with Retarded Argument - Chu Yu-ming; Cheng Jin-fa (Journal of Inequalities and Applications, 2009)
Necessary and sufficient conditions are found for oscillation of the solutions of a class of strongly superlinear and strongly sublinear differential equations of even order with retarded argument.